A plan of the city and harbour of Louisburg, with the French batteries that defended it, and those of the English shewing that, part of Gabarus Bay, in which they landed, and the ground in which the encamped during the Seige in 1745 - Richard Gridley (Surveyor); Mortimer & Co. Ottawa (Lithographer)
Lithographed to accompany the report on Canadian Archives for 1886, by Douglas Brymner, Archivist. Shows the town, harbour, and fortification of Louisbourg in the French colony of Île Royale (now part of Cape Breton Island in Nova Scotia) as it would have been during the first siege of Louisbourg in 1745. Map is divided into two main parts. The left portion is a labelled map of the fortification. The right side shows the area surrounding Louisbourg, including the Harbour of Louisbourg and part of Gabarus Bay. Regiment camps are marked, and the actions of various fleets in different areas are described. The lower right hand corner contains a small map of the entire Bay of Garbarus. Scale is ca. 1 : 21,120. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .